INTERNET OF THINGS: AUTOMATIC PLANT WATERING SYSTEM USING ANDROID - Ridwan Siskandar; Muhammad A Fadhil; Billi Rifa Kusumah; Irmansyah Irmansyah; Irzaman Irzaman (The University of Lampung, 2020)
Internet of Things (IoT) is a system that connects devices directly or indirectly to the internet. The device can work with remote control. One application of the IoT system on the watering system is able to provide an approach to the ease in the process of growth and development of plants. The research carried out was applied to an IoT-based smart plant watering device. The tool is supported with a soil moisture measuring sensor that acts as a benchmark to determine the condition of soil moisture and automatic control of the process of watering plants. The process of watering plants is scheduled in the morning and evening. Information, as long as the device is run will be displayed on the LCD and screen of an Android-based smartphone application. The data can be a comparison value to determine the suitability of soil moisture data in plants. The volume of water supplied in the watering process also affects the level of soil moisture. IoT-based smart plant sprinklers can automate watering by measuring the percentage of soil moisture as a benchmark for providing water during the watering process. Remote watering control can also be done on this tool by using a WiFi signal to the same access point that is connected to the smartphone client and microcontroller. Keyword: agriculture, automatic sprinklers, engineering, IoT